The determinants of incomes and inequality: evidence from poor and rich countries - Lakner, C (2014)
This thesis consists of four separate chapters which address different aspects of inequality and income determination. The first three chapters are country-level studies which examine (1) how incomes are shaped by spatial price differences, (2) the factor income composition, and (3) enterprise size. The final chapter analyses how income inequality changed at the global level. The first chapter investigates the implications of regional price differences for earnings differentials and inequality in Germany. I combine a district-level price index with administrative earnings data from social security records. Prices have a strong equalising effect on district average wages in West Germany, but a weaker effect in East Germany and at the national level. The change in overall inequality as a result of regional price differences is small (although significant in many cases), because inequality is mostly explained by differences within rather than between districts. The second chapter is motivated by the rapid increase in top income shares in the United States since the 1980s. Using data derived from tax filings, I show that this pattern is very similar after controlling for changes in tax unit size. Over the same period as top income shares increased, the composition of these incomes changed dramatically, with the labour share rising. Using a non-parametric copula framework, I show that incomes from labour and capital have become more closely associated at the top. This association is asymmetric such that top wage earners are more likely to also receive high capital incomes, compared with top capital income recipients receiving high wages. In the third chapter, I investigate the positive cross-sectional relationship between enterprise size and earnings using panel data from Ghana. I find evidence for a significant firm size effect in matched firm-worker data and a labour force panel, even after controlling for individual fixed effects. The size effect in self-employment is stronger in the cross-section, but it is driven by individual time-invariant characteristics. The final chapter studies the global interpersonal income distribution using a newly constructed and improved database of national household surveys between 1988 and 2008. The chapter finds that the global Gini remains high and approximately unchanged at around 0.7. However, this hides a substantial change in the global distribution from a twin-peaked distribution in 1988 into a single-peaked one now. Furthermore, the regional composition of the global distribution changed, as China graduated from the bottom ranks. As a result of the growth in Asia, the poorest quantiles of the global distribution are now largely from Sub-Saharan Africa. By exploiting the panel dimension of the dataset, the analysis shows which decile-groups within countries have benefitted most over this 20-year period. In addition, the chapter presents a preliminary assessment of how estimates of global inequality are affected by the likely underreporting of top incomes in surveys.